Transfer Characteristics of Vocal Tract Closed by Mask Cavity - VOJNOVIĆ, Milan; MIJIĆ, Miomir; ŠUMARAC PAVLOVIĆ, Dragana (Archives of Acoustics, 2018)
This paper analyses the changes in transfer characteristics of the vocal tract when closed by a mask, i.e. a chamber. The analysis was performed in two ways: by analytical estimation and by measurements in the vocal tract physical model for the case of mask with inner volume V = 430 cm3, corresponding to the oxygen masks used in combat airplanes. It was shown that closing the vocal tract with a mask cavity increases the first formant frequency by about 10% in front and high vowels (/e/, /i/, and /u/) and the frequencies of the first two formants by about 5% in the remaining two vowels (/a/ and /o/). It was also revealed that longitudinal and transversal resonances in the mask chamber can lead to errors in the recognition of the vowel formant frequencies. The results point to the need for additional knowledge about resonances in mask application.